Fine mapping of distal 1p loci reveals TP73 at D1S468 - Perri, Patrizia; Praml, Christian; Savelyeva, Larissa; Pillmann, Andrea; Schwab, Manfred (Cytogenetics and cell genetics, 1999)
In the present study we establish a FISH fine-map of 1p36.3 loci. This region is frequently altered in different types of human tumors suggesting the existence of cancer-related genes. Identification of cosmids carrying both D1S468 and TP73 sequences leads to the assignment of TP73 to the most frequently deleted locus in colon and breast cancer and integrates this gene in human genetic maps. Localization of other distal loci was determined as follows: distal-CDC2L1-D1Z2-D1S94-TP73/D1S468-D1S1615-proximal. D1S1615, earlier reported as a telomeric sequence, is considerably more proximal than previously thought.